Diarylheptanoids from Curcuma phaeocaulis Suppress IL-6-Induced STAT3 Activation - Jang, Hyun-Jae; Park, Eun-Jae; Lee, Seung-Jae; Lim, Hyung-Jin; Jo, Jin Ha; Lee, Seung Woong; Rho, Mun-Chual (Planta Medica, 2019)
Three undescribed diarylheptanoids (3–5) and six known curcuminoids (1, 2, and 6–9) were obtained from the ethyl acetate-soluble fraction of an ethanolic extract of Curcuma phaeocaulis. Their chemical structures and absolute configurations were elucidated by high-resolution electrospray ionization mass spectrometry, nuclear magnetic resonance spectroscopy, circular dichroism spectroscopy, and the modified Mosherʼs method. Previous studies constructed Hep3B cells stably transfected with pSTAT3-Luc plasmid containing STAT3 binding site to discover STAT3 inhibitors from natural products. The STAT3 inhibitory activities of all isolates were measured in transfected Hep3B cells after treatment with IL-6. Compound 5 ((5R)-1,7-Bis(3,4-dimethoxyphenyl)-3-methoxy-1-hepten-5-ol), demethoxycurcumin (7), and curcumin (8) exhibited significant inhibitory activity (IC50 values: 11.1, 1.9, and 1.6 µM, respectively). Furthermore, IL-6-induced phosphorylation of STAT3, and the mRNA expression levels of inflammation-related genes such as CRP, IL-1β, ICAM-1, and SOCS3 were significantly reduced by exposure to compound 5. These data suggested that the inhibitory activity of 5 is associated with the suppression of STAT3 phosphorylation. Thus, compound 5 may be a promising candidate for the treatment of cancer or inflammatory diseases related to the IL-6/STAT3 signaling pathway.
Keywords: Curcuma phaeocaulis; Zingiberaceae; NMR spectroscopy; diarylheptanoids; IL-6; STAT3; inflammation